Protocol A - Sampling and slaughter methods [Pratical guide of protocols: sampling procedures] - Basurco B.; Carrillo M.; Felip A.; Zanuy S.; Herráez M.P. (Advances in fish reproduction and their application to broodstock management: a pratical manual for sea bass, 2009)
Sampling procedures are commonly carried out in both laboratories and farms in order to collect samples from animals under experimentation or rearing conditions. In the laboratory, these procedures are necessary to analyse the effects of different treatments (i.e., hormonal, environmental or genetic cues among others) on fish performance under investigation. Like other scientific areas of knowledge, the reproduction area is vast and complex. In particular, the study of those factors involved in the activation of the brain-pituitary-gonad (BPG) axis is crucial for a better understanding of some biological processes related to the estimation of male and female reproductive success in fish. Accordingly, a general overview about practical considerations of how to proceed in a sampling and slaughter procedure to study reproductive aspects of this axis is described in this session. It should be noted that the equipments and protocols available in the laboratory for each species are a key issue to be considered before samples are collected. On the other hand, according to the objectives in each experiment, variations in the way to proceed in sampling and slaughter procedures may occur. A conventional procedure for sample and data collection is described in this Protocol including blood and plasma collection, dissection and tissue collection and estimation of different body indexes in the sea bass.